Endorser Laki-Laki Produk Kosmetik Perempuan Dan Pengaruhnya Terhadap Sikap Khalayak - Asprilla Riza Dwiatmaja; Pulung Setiosuci Perbawani (Program Studi Ilmu Komunikasi, 2021)
Abstract: The case of male endorser of female cosmetics product is relatively novel within the practice of marketing in Indonesia. Male and cosmetics; two concepts that are contradictory but mutually corelate. Men are understood as strong figure, masculine, and far from the association to beauty. On the other hand, cosmetics are inherently tied to the beauty itself. It becomes interesting when these two concepts are paired together within the same context of social media endorsement. This article is reporting an attempt to investigate the causative relationship between the practice of endorsement of cosmetics product by male celebrities, and how it affects the audiences’ attitude. The data used in this article is gathered through an online survey on 400 respondents. Although the notion of male and cosmetics are mutually foreign, male endorsers were seen as able to influence the attitude of the audience when looking at cosmetic endorsement, toward positive tendency. However, considering the fact that most of the male endorsers of cosmetics product have effiminate appearance, it is still safe to assume that the positive statistical value did not represents similar opinion regarding men in general and cosmetics productKeywords: endorsement, brand endorser, men, cosmetics,audience attitude